Geographic and Traffic Aspects of Possibilities for Implementing Ropeway Systems in Passenger Transport - Nikšić, Mladen; Gašparović, Slaven (Promet - Traffic&Transportation, 2012)
The paper studies the ropeways as a special subgroup of land traffic system from the interdisciplinary aspect of the traffic sciences and geography. The ropeways have seen a propulsive technical and technological development over the last several decades. Therefore, the paper gives an overview of the types of ropeways with special emphasis on the technologically most advanced ropeways. Regarding the lack of studies on the ropeway issues in Croatia, the space distribution of ropeways in the Republic of Croatia has been analysed. The ropeways, as well as other transport modes, affect the space, and since ropeways are considered environmentally friendly traffic modes, their impact on the environment is analysed, both in the mountains and in the cities. Moreover, the economic influence of ropeways on the surrounding area is studied as well.KEY WORDS: ropeway, surface lift, aerial ropeway, chairlift, gondola, funicular